Pengaruh Preferensi Konsumen dan Iklan Online terhadap Keputusan Pembelian pada Produk Skin Hero (Studi Kasus pada Mahasiswa Fakultas Ekonomi dan Bisnis di Universitas Pembangunan “Veteran” Jawa Timur) - Komang Suparyawan; Rizky Dermawan (Universitas Batanghari, 2023)
The purpose of this assessment is to determine impact. from consumer preferences and online advertising to purchase decisions. Hero skin products in mobile legends online games where this should be a tertiary need that does not have to be met first. However, many young people are more concerned with buying skin products than other long-term needs. The population in this study were Management students at the East Java